Challenges of transference links in the Covid-19 pandemic and in the post-pandemic (Praxis Educativa, 2023)
As part of the research project "Teacher’s subjectivities and transference links in the classroom", from the Psychology chair of Human Sciences College at National University of La Pampa, we systematized information from autobiographical narratives collected during the seminar “Tansference links in the neopandemic. Subjective effects on children, youth and adults and educational institutions”. The stories about school situations in pandemic, and after the return to face-to-face, enabled the analysis of the challenges of this transfer during times of exceptionality, as well as the subjective impact and link in the return to the classroom. Subjective differences, socioeconomic inequalities, affective disconnection or bond fragility, although they were observed prior to MPSI (Mandatory Preventive Social Isolation), seem to have deepened during the pandemic. Consequently, new challenges arise to strengthen the pedagogical bond in the face-to-face modality and, when applied, in the hybrid modality.
Keywords: psychology; education; transference links; Covid-19 pandemic; Pos pandemic